A Comparative Study on the Educational Barriers of Tribal Girls Students at Secondary and Higher Secondary Level - Pramanik, Dr. Bhabesh (International Journal of Formal Education, 2023)
The present study aims to find out the educational problems of tribal girls students at secondary and higher secondary level. In terms of school location, medium, and kind, it has also attempted to compare the educational issue at the secondary and higher secondary levels. The researcher has used a combination of primary and secondary sources to accomplish this. The primary data was gathered via the use of a validated structured questionnaire. Books, journals, and other secondary sources were used in order to compile this data. The study's findings indicate that indigenous girls' educational challenges at the secondary and upper secondary levels are similar. To sum up, tribal female students encounter a wide range of challenges that make it impossible for them to study or advance in their studies. In addition to seeing education as a liberating force, we must work to eliminate barriers that prevent women from gaining access to high-quality, universal education.